2021
DOI: 10.3389/fnbeh.2021.760547
|View full text |Cite
|
Sign up to set email alerts
|

TNF-ɑ Induces Methylglyoxal Accumulation in Lumbar Herniated Disc of Patients With Radicular Pain

Abstract: Lumbar disc herniation (LDH) with radicular pain is a common and complicated musculoskeletal disorder. Our previous study showed that LDH-induced methylglyoxal (MG) accumulation contributed to radicular pain. The underlying mechanisms through which MG accumulates are poorly understood. In the present study, we found that both MG and tumor necrosis factor-alpha (TNF-ɑ) levels in the herniated disc of patients with radicular pain were significantly increased, and the activity of Glyoxalase 1 (GLO1), the rate-lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Nucleus pulposus has been implicated in pain arising from herniation of spinal discs. 36 , 86 In experimental models of such pain, NP is applied to the spinal dorsal roots. Placing NP in this location may result in surgical damage to the spinal column and may also cause damage or compression of the dorsal roots themselves and dorsal root ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleus pulposus has been implicated in pain arising from herniation of spinal discs. 36 , 86 In experimental models of such pain, NP is applied to the spinal dorsal roots. Placing NP in this location may result in surgical damage to the spinal column and may also cause damage or compression of the dorsal roots themselves and dorsal root ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular ROS scavenging enzymes may also inhibit ROS/H 2 O 2 from acting as a signaling molecule within the disc, which may decrease with increasing degeneration (30). Additionally, the concentrations of TNFα (40ng/mL) and H 2 O 2 (50µM) used in this study are significantly higher than concentrations found in-vivo (TNFα: 0.05-0.15ng/mL, H 2 O 2 : 0.25μM (12,76)). Finally, NP/iAF cultures were performed at a cell ratio of 1:1, higher than the ratio of NP:iAF in bovine caudal intervertebral discs (NP:iAF ratio in-vivo is approximately 1:2 from cell isolations from bovine caudal spines, data not shown).…”
Section: Unlike Np Cells Iaf Cells Did Not Increase Intracellular Ros...mentioning
confidence: 73%
“…Extracellular ROS scavenging enzymes may also inhibit ROS/H 2 O 2 from acting as a signaling molecule within the disc, and these may decrease with increasing degeneration [40]. Secondly, the concentrations of TNFα (40ng/mL) and H 2 O 2 (50μM) used in this study are significantly higher than concentrations found in-vivo (TNFα: 0.05-0.15ng/mL, H 2 O 2 : 0.25μM [18,90]). Thirdly, sample size for most of this study was at least 3 independent biological samples (N = 3) repeated in triplicate.…”
Section: Plos Onementioning
confidence: 73%